2018
DOI: 10.3389/fendo.2018.00777
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Apoplexy Following Cinacalcet Treatment in Primary Hyperparathyroidism

Abstract: Cinacalcet, a calcimimetic drug, is considered a safe and valid option for the treatment of hypercalcemia in patients with primary hyperparathyroidism who are unable to undergo parathyroidectomy. Hypocalcemia and gastrointestinal adverse reactions are the main side effects reported in patients treated with cinacalcet. We present here the case of an 80-years-old patient with primary hyperparathyroidism treated with cinacalcet for 17 months who developed a severe and symptomatic episode of hypocalcemia requiring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Since this episode, he has no recurrences of arrhythmias. Dalmazi et al 16 reported a patient with primary hyperparathyroidism developing severe hypocalcemia, related to parathyroid adenoma infarction apparently due to cinacalcet administration. In our patient, the gradual onset of hypocalcemia, the follow‐up ultrasound findings, and complete recovery when cinacalcet was discontinued strongly suggest the hypocalcemia was not related to parathyroid infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Since this episode, he has no recurrences of arrhythmias. Dalmazi et al 16 reported a patient with primary hyperparathyroidism developing severe hypocalcemia, related to parathyroid adenoma infarction apparently due to cinacalcet administration. In our patient, the gradual onset of hypocalcemia, the follow‐up ultrasound findings, and complete recovery when cinacalcet was discontinued strongly suggest the hypocalcemia was not related to parathyroid infarction.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the fact that we were able to wean the patient off the calcium supplementation without use of active vitamin D analogs after 2.5 years from the episode of hypocal cemia suggests that the patient may have initially had dormant fifth parathyroid gland that became functionally active once the activity of 4 parathyroid glands has ceased due to surgical excision and cinacalcet exposure. In a previous case report, Di Dalmazi et al 10 described an 80yearold patient with PHPT treated with cinacalcet for 17 months at a maximum dose of 180 mg daily who developed severe and symptomatic hypo calcemia that was associated with the resolution large parathy roid adenoma. In contrast, our patient has been receiving only a very small dose of cinacalcet for a short period of time and did not have clear radiographic evidence of parathyroid adenoma(s).…”
Section: Discussionmentioning
confidence: 99%
“…However, in symptomatic cases with evidence of bone and kidney disease, surgical treatment is preferred [27,31,32,42]. Treatment with bisphosphonates and calcimimetics, such as cinacalcete, is applied in cases of severe hypercalcemia and difficulty in performing surgical treatment in a timely manner [43,44]. Therapeutic doubt arises in asymptomatic cases, in which initial surgical treatment is often not Parathyroid Glands and Hyperparathyroidism: A General Overview DOI: http://dx.doi.org /10.5772/intechopen.92785 indicated.…”
Section: Treatmentmentioning
confidence: 99%